Knowledge, attitude, perception, and factors associated with the risk perception of COVID‐19 among nursing college students in Japanese universities: A cross‐sectional study. Issue 6 (3rd November 2022) - Shimotake, Yuki; Mbelambela, Etongola Papy Steve; Muchanga, Sifa Marie Joelle; Villanueva, Antonio F.; Siburian, Marlinang Diarta; Shimomoto, Rie; Ikeuchi, Kazuyo; Matsunaga, Yoko; Minami, Marina; Iiyama, Tatsuo; Suganuma, Narufumi
Abstract: Background and Aim: The spread of coronavirus disease 2019 (COVID‐19) in the world has brought different attitudes and perceptions among social strata. Nursing students being future first‐line healthcare workers are more at risk of being infected and exposed to various stressors from shared information. The objectives of this study were to evaluate the knowledge, attitude, and perception of COVID‐19 among nursing students and to estimate predictors of their risk perception. Methods: We conducted an online survey among undergraduate nursing students at three selected Japanese Universities. Data on knowledge, attitude, and perception toward COVID‐19 were collected using a structured questionnaire. We performed multiple logistic regression analyses to identify factors associated with the risk perception toward COVID‐19 infection. Results: Of the 414 nursing students who participated in the study, 368 (90.4%) reported that the media including radio, television, internet, and/or social media were the main source of knowledge. Fever (96.1%) and dry cough (89.6%) were reported as the main symptoms. Regarding the attitude toward the treatment and preventive measures, almost 92.8% of participants recommended the use of vaccines. Being female appeared to be three times associated with the fear of getting infected (adjusted odds ratio [aOR]:3.03; 95% confidence interval [CI]: 1.21–7.58). Students who took part in extracurricular activities reported that they feared being infected with COVID‐19 (aOR:2.62; 95% CI:1.33–5.16). Other factors did not show an association. Conclusion: Knowledge and attitude of nursing students toward COVID‐19 were accurate for the majority of them, with the main source of information being the media. Practicing extracurricular activities and being female were associated with the fear of the disease. Efficient and controlled communication is needed during widespread disease outbreaks.